Development of construction waste minimisation plan in construction site / Zulikha Abdul Talib - Abdul Talib, Zulikha (2024)
Construction industry in Malaysia contributes a rapid growth in the last decade. However, the recent construction industry is undertaking pressure to practice waste minimization due to the over-production of waste. Facing problem such as money priority by contractor compared to responsible on ecosystem, existence of illegal dumping, lack of management level concern and lack of enforcement law by government lead this thesis to evaluate the strategies. The aim of this study is to identify the construction waste barrier, sources and categorisation, to evaluate the awareness of management team on construction waste issue as well as to develop construction waste minimisation plan in construction projects. A quantitative method has been adopted as the mean of data collection by distributing 100 set of questionnaire surveys to construction key player of Grade CIDB G1 until G7 and an interview with local authority in Penang. Further, the data analysis was conducted through reliability analysis and adopting Statistical Package for Social Science (SPSS) version 26. Based on the finding, timber is the most frequent construction waste produced in Penang followed by concrete and cement. Meanwhile, lack of market on recycling centre is the highest barrier factor revealed by the respondents. Apart from that, the most potential strategies proposed by respondents on construction waste minimisation is government must improve the enforcement law followed with encouraging in Building Information Modelling (BIM) application as well as to launch awareness campaign. Besides, the construction waste minimisation plan also presents a coherent approach for achieving sustainable waste minimization in construction companies.